1991
DOI: 10.1038/bjc.1991.9
|View full text |Cite
|
Sign up to set email alerts
|

Superior localisation and imaging of radiolabelled monoclonal antibody E48 F(ab')2 fragment in xenografts of human squamous cell carcinoma of the head and neck and of the vulva as compared to monoclonal antibody E48 IgG

Abstract: Monoclonal antibody (MAb) E48 and its F(ab')2 fragment, radiolabelled with 131I, were tested for tumour localisation and imaging in nude mice bearing a squamous cell carcinoma xenograft line derived from a head and neck carcinoma (HNX-HN) or from a vulva carcinoma (VX-A431). MAb IgG or F(ab')2 fragments were injected in parallel and at day 1, 2, 3 and 6 or 7, mice were either scanned with a gamma camera or dissected for determination of isotope biodistribution. In HNX-HN bearing mice, E48 IgG as well as F(ab')… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…In our study, we observed higher tumour to non-tumour ratios after administration of radiolabelled F(ab')2 fragments compared with IgG. Other investigators demonstrated improved immunoscintigraphic detection of experimental tumours using radiolabelled fragments (Buchegger et al, 1983;Hansson et al, 1988;Gerretsen et al, 1991). Thus far, clinical data from radioimmunodetection of cancer confirmed an increase in sensitivity for F(ab')2 fragments compared with intact IgG (Lamki et al, 1990).…”
Section: Biodistribution Of Mabs Andfragmentssupporting
confidence: 72%
“…In our study, we observed higher tumour to non-tumour ratios after administration of radiolabelled F(ab')2 fragments compared with IgG. Other investigators demonstrated improved immunoscintigraphic detection of experimental tumours using radiolabelled fragments (Buchegger et al, 1983;Hansson et al, 1988;Gerretsen et al, 1991). Thus far, clinical data from radioimmunodetection of cancer confirmed an increase in sensitivity for F(ab')2 fragments compared with intact IgG (Lamki et al, 1990).…”
Section: Biodistribution Of Mabs Andfragmentssupporting
confidence: 72%
“…This mAb E48 is also reactive with normal squamous epithelia and squamous cell carcinomas and has a similar tumour selectivity in xenografted nude mice to that seen for mAb K984 in this study [11,12,27]. Preliminary results of this clinical study look very promising and demonstrate that the 99mTc-labelled E48 F(ab')2 conjugate is capable of detecting lymph node metastases (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 57%
“…For diagnosis and therapy of SCC of the head and neck, monoclonal antibodies (mAbs) directed to tumour-associated cell-surface antigens are potentially powerful tools [7,16]. Among the potential applications of such tumour-preferential mAbs is their use as targeting agents for the selective delivery of radionuclides [2,8,11,12,17,20,22,27] or anti-tumour agents [2,9,10,15,25,37] to primary tumours and particularly to lymph node and distant metastases. Other approaches make use of unconjugated mAbs that eliminate tumour cells by activating immunological effector mechanisms, or mAbs that block mmour-associated processes, like proliferation and metastases, by binding to cell-surface receptors directly involved in these processes [13,33,36,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…We also developed an affinity purified polyclonal antibody raised against the 85 kD LOXL4 antigen to demonstrate its expression in HNSCC tissues of different grading and staging, and studied its involvement in the structural organisation of squamous epithelia . So far, most of the described antibodies against HNSCC showed considerable cross reactivity with normal tissue or showed only reactivity with SCC of distinct sites of origin . The first successful radioimmunotherapy results for HNSCC were shown with the E48 mAb in the early 1990 sec .…”
mentioning
confidence: 99%